б) 1. Находим D ( дискриминант = b^2 -4*a*c ) = 169 + 56 = 225 ( √225= 15 ) 2. Находим x1 = ( -b + √D) / 2a = (-13 + 15) / 4 = 0.5 3. Находим x2 = (-b - √D) /2a =( -13-15) / 4= -7 4. 2x^ +13x -7 = 2( x -0.5 ) ( x +7)

Ответы и объяснения

2013-11-17T06:21:54+00:00
А) 1. Находим Дискриминант: b^2 -4 *a*c = 25^2 * ((- 4 )* 3 * ( - 28) = 625 + 336 = 961 ( √961 = 31 )
2. Находим x1 = (-b +√D) / 2a = ( 25 + 31) / 9 = 56 / 9.
3. Находим x2 = (-b -√D ) / 2a = (25 - 31) / 9 = -6/9.
4. Тогда: 3x^2 -25x -28 = 3(x - 56/9) ( x +6/9)